Forensic study of skin post-mortem changes as a supplementary test to determine post-mortem interval (first 78 hours) (2016)
Introduction: Determining the post-mortem interval is usually based on macroscopic-morphological criteria (cadaveric phenomena); some other objective methods are often difficult to access in daily practice; therefore, we analyze the usefulness of the histopathological examination of the skin as a supplementary me-thod for determining the post-mortem interval. Materials and methods: 23 patients and 92 skin biopsies were analyzed. All samples were taken in a maximum time of 6 h post-mortem. Biopsies were classified into 4 groups according to the post-mor-tem interval, with 23 biopsies in each group: 1 (1 to 6 h); 2 (25 to 30 h); 3 (49 to 54 h); 4 (73 to 78 h); 21 histological criteria were analyzed with Fisher test and principal component analysis. Results: Skin biopsies of 23 corpses (mean age 51.6 years, 15 males and 8 females) were studied. 21 histological criteria were analyzed by Fisher test; statistical significance (p <0.001) with a reliability of 94.61% was achieved in 15 parameters. With the 15 selected parameters, a principal component analysis established that there were differences among the 4 analyzed groups. Conclusions:The skin histological changes may be used as a supplementary parameter in the forensic evaluation of the early post-mortem interval.